Avatar of transgression: Hamsun's Munken Vendt - Buttry, Dolores (Nordlit, 2009)
Knut Hamsun's play Munken Vendt may be considered a compendium of transgression of many kinds. We see in the play sexual transgression, violence, blasphemy, transgression of social rules (theft, opposition to class divisions), as well as the crossing of boundaries. The protagonist can be seen as an anticipation of the French writer Georges Bataille -- the former Catholic turned libertine fascinated with evil. Aesthetic transgression is evident as well: Hamsun transgressed against rules of style and genre in writing his monstrous eight-act verse play. The play is a confused cry of revolt.
Keywords: Knut Hamsun; Munken Vendt; transgression; revolt; vitalism; sadism; religion